Upregulated H-Current in hyperexcitable CA1 dendrites after febrile seizures - Dyhrfjeld-Johnsen, Jonas; Morgan, Robert J.; Földy, Csaba; Soltesz, Ivan (Frontiers in Cellular Neuroscience, 2008)
Somatic recordings from CA1 pyramidal cells indicated a persistent upregulation of the h-current (Ih) after experimental febrile seizures. Here, we examined febrile seizure-induced long-term changes in Ih and neuronal excitability in CA1 dendrites. Cell-attached recordings showed that dendritic Ih was significantly upregulated, with a depolarized half-activation potential and increased maximal current. Although enhanced Ih is typically thought to be associated with decreased dendritic excitability, whole-cell dendritic recordings revealed a robust increase in action potential firing after febrile seizures. We turned to computational simulations to understand how the experimentally observed changes in Ih influence dendritic excitability. Unexpectedly, the simulations, performed in three previously published CA1 pyramidal cell models, showed that the experimentally observed increases in Ih resulted in a general enhancement of dendritic excitability, primarily due to the increased Ih-induced depolarization of the resting membrane potential overcoming the excitability-depressing effects of decreased dendritic input resistance. Taken together, these experimental and modeling results reveal that, contrary to the exclusively anti-convulsive role often attributed to increased Ih in epilepsy, the enhanced Ih can co-exist with, and possibly even contribute to, persistent dendritic hyperexcitability following febrile seizures in the developing hippocampus.